REGULATORY TRANSFORMATION OF ENVIRONMENTAL IMPACT ASSESSMENT IN INDONESIA: NGF and MACTOR Analysis - Farid Mohammad; Surjono Hadi Sutjahjo; Hefni Effendi; Imas S. Sitanggang; Dwi P. Sasongko (Al-Risalah, 2026)
Since 1986, Indonesia’s Environmental Impact Assessment (EIA/AMDAL) regime has undergone successive regulatory reforms. The main problem is that environmental approval has increasingly shifted from a substantive environmental safeguard toward a more procedural and licensing-oriented instrument, raising concerns over declining assessment quality and narrower public participation. This study aims to evaluate the direction of that regulatory transformation and to explain the actor dynamics that sustain it. The study examines five major Government Regulations on EIA in Indonesia: GR No. 29 of 1986, GR No. 51 of 1993, GR No. 27 of 1999, GR No. 27 of 2012, and GR No. 22 of 2021. Using an exploratory sequential mixed-methods design, data were collected through regulatory document review, in-depth interviews with 9 senior EIA experts, and Focus Group Discussions with 25 multi-sectoral stakeholders. The data were analyzed through content analysis using the Next Generation Framework (NGF) and prospective stakeholder analysis using MACTOR (Méthodologie des Acteurs, Objectifs, Rapports de force). The findings show a clear policy shift from substantive environmental assessment to procedural efficiency, particularly under risk-based and digitally integrated licensing. NGF results indicate a decline in technical and participatory quality, while MACTOR reveals that proponents, EIA consultants, and government agencies are the dominant actors shaping regulatory outcomes. These findings imply that current reforms strengthen administrative efficiency but risk weakening the legal-protective function of EIA. The study recommends restoring substantive assessment criteria, improving data-validation capacity in digital systems, and expanding participatory rights beyond directly affected communities.